PEMAHAMAN DAN SIKAP GURU WANITA TENTANG INFORMASI BALITA SEHAT DAN POLA PENGASUHAN ANAK DI KOTA KUPANG - Salvador Guterres; Jeanny Maria Fatima (KAREBA : Jurnal Ilmu Komunikasi, 2011)
Abstract This research aims to know the difference levels of knowledge and attitude of female teachers toward the examination of the information content of under- five’s health and the children taking care pattern through interpersonal communication and mass media. This research was conducted by using pre-experimental design. In this experiment, the multistage sampling was used to determine the number of respondents. So there was 28 respondents. So there was 28 respondents which conducted to be tested. The pretest and posttest was used was used to know how far the levels of knowledge and attitude of the female teachers in achieving the information of the under-five’s health and the children taking care pattern in Kupang Municipal. The research result shows that the levels and attitude of female teachers positively changed after conveying the information of the under-five’s health and children taking care pattern through interpersonal communication and mass media. Besides that, there was the difference level of score of knowledge and attitude of female teachers in the information content which consists of giving nutrient to the children (PMA) and the actual pattern of taking care (PPA) of them.Abstrak Penelitian bertujuan untuk mengetahui tingkat perbedaan pengetahuan dan sikap guru-guru perempuan terhadap isi informasi kesehatan anak-anak melalui media massa dan saluran komunikasi antarpersonal. Penelitian ini dirancang dengan menggunakan metode eksperimental murni. Dalam eksperimen digunakan multistage sampling yang digunakan untuk menetapkan jumlah responden. Ada 28 orang responden yang ditetapkan untuk diuji. Pada uji awal dan uji akhir dilakukan untuk mengetahui sejauh mana tingkat pengetahuan dan sikap guru-guru perempuan di kota Kupang bisa memperoleh informasi balita dan pola pengasuhan anak. Hasil penelitian memperlihatkan bahwa informasi balita dan pola pengasuhan anak sebagian besar mereka peroleh melalui saluran-saluran komunikasi interpersonal (dari mulut ke mulut) dan juga media massa. Selain itu terdapat perbedaan tingkat skor pengetahuan dan sikap di kalangan para guru perempuan terhadap isi informasi yang mereka terima, terutama dalam hal pemberian makanan yang bergizi dan pola pengasuhan anak.